Mesoporous TiO2 implanted ZnO QDs for the photodegradation of tetracycline: material design, structural characterization and photodegradation mechanism - Iqbal, Anwar; Saidu, Usman; Sreekantan, Srimala; Ahmad, Mohammad Norazmi; Rashid, Marzaini; Ahmed, Naser M.; Danial, Wan Hazman; Wilson, Lee D. (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
A sol-gel method was used to prepare a mesoporous TiO2 implanted with a ZnO quantum dot photocatalyst (TZQ) for the photodegradation of tetracycline (TC) under fluorescent light irradiation. Scanning electron microscopy (SEM) shows the presence of cavities on the photocatalyst surface due to the use of starch as a synthetic template, where the nitrogen sorption results indicate that TZQ contains mesopores with reduced size (ca. 4.3 nm) versus the pore size of the parent meso-TiO2 (ca. 7.5 nm). The addition of ZnO quantum dots (QDs) resulted in spherically-shaped binary composite particles in layers onto the surface of TiO2. The coexistence of the ZnO QDs and TiO2 phase was observed using high resolution-transmission electron microscopy (HR-TEM). The photodegradation of TC was carried out in a homemade reactor equipped with two fluorescent lights (24 W each) and within 90 min of irradiation, 94.6% of TC (40 mg L−1) was photodegraded using 250 mg L−1 of TZQ at pH 9. The major reactive oxygen species identified from the scavenging tests were O2 •− followed by HO•. The deconvolution of the photoluminescence spectrum of TZQ indicates the presence of a strong quantum confinement effect (QCE) of the ZnO QDs, a defect related to Ti-species and oxygen. The analysis of the intermediates detected by LC-time-of-flight/mass spectrometry (LC/TOF-MS) suggest two photodegradation pathways. The pathways were validated using the Fukui function approach and the Wheland localisation approach. This simple and efficient photocatalytic technology is anticipated to benefit small-scale animal husbandries and aquaculture operators that have limited access to sustainable water treatment technology